Autonomous transposition of gypsy mobile elements and genetic instability in Drosophila melanogaster. - Kim, A.I.; Belyaeva, E.S.; Aslanian, M.M. (Molecular and General Genetics, 1990)
The laboratory mutator strain (MS) of Drosophila melanogaster is characterized by an elevated frequency of spontaneous mutation (10(-3)-10(-4). Mutations occur in both sexes at premeiotic stages of germ cell development. The increased mutability is a characteristic feature of MS itself, since it appears in the absence of outcrossing. Most of the mutations arising in this strain are unstable: reversions to wild type, high frequency mutation to new mutant states and replicating instability were observed. We have investigated the localization of the transposable genetic elements mdg1, 412, mdg3, gypsy (mdg4), copia and P in the X chromosomes of the MS and in the mutant lines y, ct, sbt derived from it by in situ hybridization. The P element was not found in any of these strains. The distributions of mdg1, 412, mdg3 and copia were identical in the X chromosomes of the MS and its derivatives. However, the sites of hybridization with gypsy differ in the various lines tested. In the polytene chromosomes of MS animals significant variation in location and number of copies of the gypsy element was demonstrated between different larvae; copy numbers as high as 30-40 were observed. These results suggest autonomous transposition of gypsy in the MS genome while several other mobile elements remain stable.